Redescription of holotypes of four Alopecosa species (Araneae, Lycosidae) from China - Jia Tang; Xiang Xu; Haiqiang Yin; Yuri M. Marusik; Zongguang Huang (PENSOFT PUBLISHERS, 2022)
The holotypes of four species of Alopecosa Sundevall, 1833 described from China, A. disca Tang, Yin & Yang, 1997 (female); A. orbisaca Peng, Yin, Zhang & Kim, 1997 (female); A. wenxianensis Tang, Yin & Yang, 1997 (male), and A. xilinensis Peng, Yin, Zhang & Kim, 1997 (female), are reexamined. Detailed descriptions, illustrations, remarks, and a distribution map of the three valid species are given. Alopecosa xilinensis syn. nov. is found to be junior synonym of Alopecosa licenti (Schenkel, 1953).